What is the impact of vitamin D supplementation on glycemic control in people with type-2 diabetes: a systematic review and meta-analysis of randomized controlled trails - Mohammad Ashraf Farahmand; Elnaz Daneshzad; Teresa T. Fung; Fawzia Zahidi; Maryam Muhammadi; Nick Bellissimo; Leila Azadbakht (BMC Endocrine Disorders, 2023)
Abstract Background There is conflicting evidence on the effect of vitamin D on glycemic control. Therefore, in the current meta-analyses, we aimed to assess the effect of vitamin D supplementation on the glycemic control of type 2 diabetes (T2D) patients. Methods We conducted a comprehensive search in electronic databases including; PubMed/Medline, Web of Science, Scopus, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and NIH’s Clinical Trials Registry, from the inception of each database up to January first, 2021. Results A total of 46 randomized controlled trials (RCTs) consisting of 2164 intervention subjects and 2149 placebo controls were included in this meta-analysis. Pooled analyses for HbA1c showed a significant change between the intervention and placebo group, the weighted mean difference (WMD)(95% confidence interval(CI)) was -0.20%(-0.29, -0.11) with P < 0.001. Analyses for assessing changes in FPG found a significant reduction in the intervention group after vitamin D supplementation, the WMD (95%CI) was -5.02 mg/dl (-6.75,-3.28) with P < 0.001. The result of pooled analyses for HOMA-IR revealed a significant change between the intervention and control group, the WMD (95%CI) was -0.42(-0.76, -0.07) with P = 0.019. The subgroup analyses showed the most efficacy in a higher dose and short intervention period and in subjects with deficient vitamin D status. Conclusion Vitamin D supplementation might be beneficial for the reduction of FPG, HbA1c, and HOMA-IR in type 2 diabetes patients with deficient vitamin D status. This effect was especially prominent when vitamin D was given in large doses and for a short period of time albeit with substantial heterogeneity between studies and a probability of publication bias.